Early application of percutaneous vertebroplasty reduces pain without affecting peripheral blood stem cell (PBSC) collection and transplant in newly diagnosed multiple myeloma (MM) patients. (2nd December 2013) - Tosi, P.; Sintini, M.; Molinari, A.L.; Imola, M.; Ciotta, G.; Tomassetti, S.; Mianulli, A.M.; Ratta, M.; Mangianti, S.; Merli, A.; Polli, V.
<x xml:space="preserve">Abstract</x> Vertebral fractures occur in over 60% of newly diagnosed multiple myeloma (MM) patients and can cause pain, disability and poor quality of life. Antimyeloma therapy can lead to symptoms improvement, but these effects can take time to be perceived. Application of radiotherapy prior to peripheral blood stem cells (PBSC) mobilisation can impair stem cell collection. Percutaneous vertebroplasty has been proposed as a suitable option to rapidly relieve bone pain from vertebral fractures in MM patients, but, little is known about the effects of this procedure on subsequent PBSC mobilisation, collection and transplant. Eighteen patients (10M/8F, median age 64.5 years) with untreated MM and painful vertebral lesions underwent vertebroplasty prior to proceed to the planned transplant program at our Institution. Forty‐one procedures were performed at C2‐L5 levels, eight patients were treated at ≥2 levels. Ninety‐five per cent of the cases obtained a complete or optimal pain control. All the patients successfully mobilised PBSC (median CD34+ cells = 10.8 × 106/kg) and underwent autologous PBSC transplant; both polymorphonucleates and platelets recovery averaged 11 days. Our data seem to suggest that percutaneous vertebroplasty is useful in newly diagnosed MM patients with painful vertebral fractures as it allows rapid and durable achievement of pain control, without interfering with further treatment.